PENGARUH PENANAMAN SENGON (Paraserianthes falcataria) TERHADAP KANDUNGAN C DAN N TANAH DI DESA SLAMPAREJO, JABUNG, MALANG - Ulyan Khalif; Sri Rahayu Utami; Zaenal Kusuma (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2014)
Landuse change are suspected to be one responsible to soil fertility decline on Slamparejo, Jabung, Malang. Efforts done by local farmers to deal with these problems are plantation of P. falcataria trough a reforestation program around 2003-2004. The benefits of the program are still need to be assessed so that this research was done (1) to compare the soil quality between P. falcataria-planted field and no P.falcataria field by the parameters of soil organic matter content and available N, (2) to study the relationship between organic matter input and soil organic matter content and available N, and (3) to identify factors affecting N availability post-P. falcataria plantation.This research used randomized block design with 5 treatments (annual crop field, 3 and 6 years P. falcaria plantation field, agroforestry field with P. falcataria + coffee + talas plantation, and ex-P. falcataria-planted field. Soil were sampled compositely by 3 replication from 0-20 cm depth. Litter were sampled from a 0.5m2 sub-plot of each treatment.Results showed that P. falcataria plantations enhance soil fertility indicated by increased soil organic matter input to 10.6 times (monoculture) and 17.6 times (agroforestry) control, increased soil organic matter content by 1.5 times (monoculture) and 2.3 times (agroforestry) control, increased total N of 1.6 times (monoculture) and 2.4 times (agroforestry) control, increased ammonium by 1.7 times (monoculture) and 3.2 times (agroforestry) control, and increased nitrate by 2.4 times (monoculture) and 3.9 times (agroforestry) control. The increased soil N content of P. falcataria-planted field were caused by higher soil organic inputs compared to those with no P. falcataria plantation. Nitrogen availability affected by soil texture but have no relationship with soil pH. However, agroforestry fields showed higher pH, organic C, total N, and available N than monoculture P. falcataria fields. Measured soil chemical properties showed no significant change by the increase of P. falcataria age, moreover, they declined down towards control on ex-P. falcataria plantation. This indicates that reforestation would only give a temporary soil quality enhancement.Key words: Regreening, Paraserianthes, Agroforestry, Soil organic matter, nitrogen total